2017
DOI: 10.1186/s13287-017-0638-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming converts human Wharton’s jelly mesenchymal stem cells into functional cardiomyocytes by differential regulation of Wnt mediators

Abstract: BackgroundLineage commitment of mesenchymal stem cells (MSCs) to cardiac differentiation is controlled by transcription factors that are regulated by epigenetic events, mainly histone deacetylation and promoter DNA methylation. Here, we studied the differentiation of human Wharton’s jelly MSCs (WJMSCs) into the cardiomyocyte lineage via epigenetic manipulations.MethodsWe introduced these changes using inhibitors of DNA methyl transferase and histone deacetylase, DC301, DC302, and DC303, in various combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…Yet, it was shown that cytokines like BMP4, IL and TGF improve cardiac development of human and non-human MSCs [57,77]. However, the cardiomyocyte-like cells derived from these programmed MSCs lack profound sarcomere formation, beating activity and physiological maturation [78,79]. This is in accordance to our data indicating that mRNA transfection could promote the expression of early cardiac proteins, while differentiation efficiency and elaboration of a terminal cardiac phenotype is profoundly limited when compared to PSC differentiation protocols [27,31].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it was shown that cytokines like BMP4, IL and TGF improve cardiac development of human and non-human MSCs [57,77]. However, the cardiomyocyte-like cells derived from these programmed MSCs lack profound sarcomere formation, beating activity and physiological maturation [78,79]. This is in accordance to our data indicating that mRNA transfection could promote the expression of early cardiac proteins, while differentiation efficiency and elaboration of a terminal cardiac phenotype is profoundly limited when compared to PSC differentiation protocols [27,31].…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of reprogramming studies have focused on fibroblasts as the somatic cell source, several studies have recently demonstrated the feasibility of reprogramming MSCs. 4,13,14 Human umbilical cord tissue is readily available, easily procured without invasive procedures, and does not elicit ethical debate. Cai et al 3 reported the generation of iPSCs from UC-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two centuries, with the development of the electromagnetic theory, there has been a surge increase in the interest to the interaction of electromagnetic fields (EMFs) and various life processes. Particularly into the 20th century, plenty of bio-effects of electric, magnetic, and electromagnetic fields on human beings, animals and cells have been described either in vitro or in vivo conditions (Berg 1997, Berg 1999, Hönes Vol. 68 et al 1998.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In vitro stem cell differentiation can be induced by chemical stimuli, such as small molecules that act modifying self-renewal, inducing cell differentiation and reprogramming (Ding and Schultz 2004, Mansour et al 2012, Mattout et al 2011. Stem cell fate is controlled by multiple signaling pathways, involving miRNAs (Gangaraju andLin 2009, Balzano et al2018), and other epigenetic events, such as DNA methylation and chromatin remodeling, still not completely yet understood (Lacagnina 2019, Bhuvanalakshmi et al 2017, He et al 2019. Growth factors, hormones, cytokines and other pharmacological agents can be added to the culturing medium to influence stem cell commitment toward specific phenotype (Christ et al 2013, Maioli et al 2016a.…”
Section: Influence On Genes and Epigeneticsmentioning
confidence: 99%